How do different noise pollution sources affect apartment prices? - Trojanek, Radoslaw (International Journal of Strategic Property Management, 2023)
The paper analysed the impact of different noise sources on the residential market. This research used the hedonic method in OLS, SAR and SEM models based on the data set containing geocoded 16,247 apartments in Poznan. Strong evidence was found that noise is negatively linked with apartment prices. The apartment prices were the most significantly influenced by railway noise – an increase of 1 dB above 55 dB causes a 1.79% decrease in the value of an apartment. For other noise sources, aviation noise had the most significant impact with a 0.59% decrease in value per dB, tram noise with a 0.32% decrease and road noise with a 0.12% decrease. The influence of different noise levels on apartments is not constant and does not assume a linear relationship. For road noise, noise below 60 dB and tram noise below 65 dB were statistically insignificant. This may indicate that these noise levels are acceptable and are compensated by better access to public roads or urban transport.